Exploring Transitivity in English Education Students’ Argumentative Writing - Muhammad Daffa Arya Kusuma; Yogi Setia Samsi; Revina Pinkan Septiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Argumentative writing is an essential skill for English Education students, yet many still struggle to construct logical and persuasive arguments. This study examines how students use transitivity processes to build arguments through the framework of Systemic Functional Linguistics (SFL). A descriptive qualitative approach was employed to analyze four argumentative essays consisting of 44 clauses written by second-year English Education students at Universitas Singaperbangsa Karawang. Each clause was categorized according to Halliday and Matthiessen’s (2004) transitivity system. The analysis revealed that material processes occurred 31 times, mental processes 5 times, relational processes 6 times, and verbal, behavioral, and existential processes 2 times in total. These findings show that students predominantly describe actions rather than abstract reasoning or evaluations. Pedagogically, the results suggest two key implications, first, integrating functional grammar awareness into academic writing instruction can help students understand how language constructs meaning; second, designing writing tasks that emphasize varied process types can enhance students’ argument quality and critical thinking.